2014
DOI: 10.1007/s10230-014-0286-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Geochemistry of Acid Mine Drainage

Abstract: Due to geochemical similarity between arsenic and sulphur, polymetallic sulphide deposits and pyrite/ arsenopyrite-bearing coal beds often contain exceptionally high concentrations of arsenic. Arsenic release from mine waste occurs after oxidative dissolution of sulphide minerals. Both arsenite and arsenate forms coexist in many mine drainage localities, with the latter oxidation state more common. The rate of arsenite oxidation to arsenate in such environments is mostly controlled by the availability of oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 81 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…Arsenic is ubiquitous in acid mine drainage (AMD) (Williams, 2001;Paikaray, 2015) and 51 represents a severe threat for freshwater resources downstream from mining sites. It is 52 therefore essential to develop treatment processes able to remove arsenic from mine waters.…”
Section: Introduction 50mentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic is ubiquitous in acid mine drainage (AMD) (Williams, 2001;Paikaray, 2015) and 51 represents a severe threat for freshwater resources downstream from mining sites. It is 52 therefore essential to develop treatment processes able to remove arsenic from mine waters.…”
Section: Introduction 50mentioning
confidence: 99%
“…Alternatively, biological oxidation of iron and arsenic occurs naturally in AMD and has been 62 observed at various mining sites worldwide (Casiot et al, 2003;Asta et al, 2010b;Egal et al, 63 2010;Chen and Jiang, 2012;Paikaray, 2015). Bacteria involved in iron and arsenic oxidation 64 have been isolated and their metabolic capacities investigated (Battaglia-Brunet et al 2002, 65 Bruneel et al, 2003.…”
Section: Introduction 50mentioning
confidence: 99%
“…The release of As into the environment due to anthropogenic activities also contributes to high As concentrations. Mining activity exposes reduced As-minerals to the environment that will undergo weathering (with As concentrations in acid rock drainage of up to 11.3 mM (Paikaray 2015)). As-product manufacturing will also contribute to contamination of soil and water bodies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, release of elements from contaminated sediment is effected by environmental conditions such as pH, phosphate, redox conditions, and time (Rubinos et al 2011;Molinari et al 2014;Dang et al 2014). Although there are many studies about As mobilization and release from soils or sediments in mining areas (Paikaray 2015;Macgregor et al 2015;Desbarats et al 2015), quantitative information regarding the leaching of As in stream sediment in mining areas, particularly under hydrodynamic conditions, is rare.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that as many as 60-100 million people globally may be at risk of exposure to excessive levels of As (Ng et al 2003). With the rapid development of the mining and smelting industry, elevated concentrations of As in natural waters, soils, and sediments associated with mine water, beneficiation wastewater, and mine tailings (Paikaray 2015;Desbarats et al 2015). Gaur et al (2005) found that As discharged into the stream water can precipitate and accumulate onto stream sediment and eventually enter the food chain.…”
Section: Introductionmentioning
confidence: 99%